2015
DOI: 10.1177/1687814015589458
|View full text |Cite
|
Sign up to set email alerts
|

Research on carbon fiber–reinforced plastic bumper beam subjected to low-velocity frontal impact

Abstract: Lightweight and safety performance of automobiles are two important factors for automobile designs. In this article, a research on lightweight and crashworthiness of automotive bumper has been conducted. The carbon fiber-reinforced plastic bumper beam is considered to replace the traditional high-strength steel one. The low-velocity impact finite element simulations for the above two bumper beams are performed via LS-DYNA. Furthermore, the energy absorption capabilities and dynamic response characteristics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 9 publications
1
8
0
1
Order By: Relevance
“…But this does not mean that a beam with a smaller thickness is better because the stress on the beam increases with the use of less thickness. erefore, from the above results, and literature observations it can be concluded that neither a beam with less thickness nor one with higher thickness is better; instead, it depends on the application it is required for [21]. e main purpose of this investigation is to select a lightweight side bumper beam without sacrificing the impact behavior.…”
Section: Impact Forcementioning
confidence: 84%
“…But this does not mean that a beam with a smaller thickness is better because the stress on the beam increases with the use of less thickness. erefore, from the above results, and literature observations it can be concluded that neither a beam with less thickness nor one with higher thickness is better; instead, it depends on the application it is required for [21]. e main purpose of this investigation is to select a lightweight side bumper beam without sacrificing the impact behavior.…”
Section: Impact Forcementioning
confidence: 84%
“…The À 121:7r 2 3 + 40:5r 2 4 + 31:2x 1 x 2 À 19:5x 1 x 3 À 51:7x 1 r 1 À 52:6x 2 x 3 À 70:3x 2 r 1 + 85:8x 2 r 2 À 39:2x 2 r 3 À 59:3x 2 r 4 À 44:1x 3 r 1 À 17:3x 3 r 2 + 129:2x 3 r 3 + 84:6x 3 r 4 + 165:2r 1 r 2 + 44:5r 1 r 3 À 168:2r 1 r 4 + 132:8r 2 r 3 + 23:3r 2 r 4 À 350:0r 3 r 4 ðA:4Þ F multiÀmat = 64:6 À 204:5x 1 À 310:7x 2 + 94:7x 3 + 2155:4r 1 À 382:9r 2 À 335:1r 4 + 106:1x 2 1 + 358:8x 2 2 + 26:3x 2 3 À 797:4r 2 1 À 820:7r 2 2 + 129:6r 2 3 + 214:7r 2 4 À 30:4x 1 x 2 À 80:0x 1 x 3 À 344:4x 1 r 1 À 428:9x 1 r 2 + 180:6x 1 r 3 + 455:2x 1 r 4 À 194:9x 2 x 3 À 97:5x 2 r 1 + 24:9x 2 r 2 À 358:5x 2 r 3 + 394:0x 2 r 4 À 27:5x 3 r 4 + 142:3x 3 r 3 + 318:5x 3 r 4 + 3146:9r 1 r 2 À 565:0r 1 r 3 À 2399:5r 1 r 4 + 770:9r 2 r 3 À 638:8r 2 r 4 À 832:3r 3 r 4 ðA:5Þ L multiÀmat = 454:5 À 456:5x 1 À 313:2x 2 À 29:3x 3 + 2975:6r 1 À 999:3r 2 À 173:4r 3 + 131:4r 4 + 249:4x 2 1 + 435:3x 2 2 + 46:9x 2 3 À 593:0r 2 1 À 1218:3r 2 2 À 1242:7r 2 3 + 480:5r 2 4 + 171:9x 1 x 2 À 198:6x 1 x 3 À 733:9x 1 r 1 À 638:3x 1 r 2 + 210:4x 1 r 3 + 540:0x 1 r 4 À 426:3x 2 x 3 À 331:2x 2 r 1 + 584:0x 2 r 2 À 698:2x 2 r 3 + 66:4x 2 r 4 À 179:8x 3 r 1 À 137:0x 3 r 2 + 945:4x 3 r 3 + 707:2x 3 r 4 + 3453:5r 1 r 2 + 330:8r 1 r 3 À 3492:7r 1 r 4 + 2237:6r 2 r 3 À 432:0r 2 r 4 À 2631:2r 3 r 4 ðA:6Þ…”
Section: Declaration Of Conflicting Interestsunclassified
“…Wang and Li 1 conducted design and analysis of automotive carbon fiber composite bumper beam based on finite element analysis (FEA). Hu et al 2 made a research on carbon fiber-reinforced plastic bumper beam subjected to low-speed frontal impact. Michael et al 3 studied the expanded polypropylene foam energy management for bumper system.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, a lot of studies have been done on the beam or the crash box by novel material structure [2][3][4][5][6][7] or the optimization design [8][9][10] or structure improvement of the shape, thickness, section structure, [11][12][13][14] etc. 15,16 These researches mainly focus on the low-speed crashworthiness, which can make the bumper system possess enough stiffness and strength so as to protect the body parts and occupants in the car collision. But for the pedestrians, too large bumper stiffness is bound to increase the damage degree of the pedestrian lower leg in the collision accident.…”
Section: Introductionmentioning
confidence: 99%